GABRB1 Single Nucleotide Polymorphism Associated with Altered Brain Responses (but not Performance) during Measures of Impulsivity and Reward Sensitivity in Human Adolescents - Duka, Theodora; Nikolaou, Kyriaki; King, Sarah L.; Banaschewski, Tobias; Bokde, Arun L. W.; Büchel, Christian; Carvalho, Fabiana M.; Conrod, Patricia J.; Flor, Herta; Gallinat, Jürgen; Garavan, Hugh; Heinz, Andreas; et al. (Frontiers in Behavioral Neuroscience, 2017)
Variations in genes encoding several GABAA receptors have been associated with human drug and alcohol abuse. Among these, a number of human studies have suggested an association between GABRB1, the gene encoding GABAA receptor 1 subunits, with alcohol dependence, both on its own and comorbid with other substance dependence and psychiatric illnesses. In the present study, we hypothesised that the GABRB1 genetically-associated increased risk for developing alcoholism may be associated with impaired behavioural control and altered sensitivity to reward, as a consequence of altered brain function. Exploiting the IMAGEN database (Schumann et al, 2010), we explored in a human adolescent population whether possession of the minor (T) variant of the single nucleotide polymorphism rs2044081 is associated with performance of tasks measuring aspects of impulsivity, and reward sensitivity that are implicated in drug and alcohol abuse. Allelic variation did not associate with altered performance in either a stop-signal task (SST), measuring one aspect of impulsivity, or a monetary incentive delay (MID) task assessing reward anticipation. However, increased fMRI BOLD response in the right hemisphere inferior frontal gyrus, left hemisphere caudate/insula, and left hemisphere inferior temporal gyrus during MID performance was higher in the minor (T) allelic group. In contrast, during SST performance, the BOLD response found in the right hemisphere supramarginal gyrus, right hemisphere lingual and left hemisphere inferior parietal gyrus indicated reduced responses in the minor genotype. We suggest that β1-containing GABAA receptors may play a role in excitability of brain regions important in controlling reward-related behaviour, which may contribute to susceptibility to addictive behaviour.